Stosunek ukraińskich partii politycznych Galicji Wschodniej do komunistów (1919-1929) - Pyrig, Marianna (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article analyzes relations between communist forces and legal Ukrainian political parties on the territory of the Eastern Galicia and Volhynia during the period of 1920s. Ukrainian communists were ready to cooperate only with socialist parties (mainly Ukrainian Social Democratic Party (USDP). Their particular goal was to subordinate these structures and organizations and coordinate their activities. This was the main way to take part in the legal political life of the region. In the middle of 1920s, it was clear that procommunist tendencies would not dominate in other, even left, parties. None of the Ukrainian legal political parties wanted to cooperate with left radical movement, considering them as agents of Moskow and Warsaw, and enemies of Ukrainians in Poland. This position defined the character of the relation between Ukrainian forces in the inter-war period in Poland.